Simulating the fate and transport of nursery‐box‐applied pesticide in rice paddy fields. Issue 6 (16th September 2015) - Boulange, Julien; Thuyet, Dang Quoc; Jaikaew, Piyanuch; Watanabe, Hirozumi
Abstract: BACKGROUND: The Pesticide Concentration in a Paddy Field model (PCPF‐1) was modified by adding a root zone compartment to simulate nursery‐box‐applied (NB‐applied) pesticide. The PCPF‐NB model was validated for predicting the concentrations of NB‐applied fipronil and imidacloprid in rice paddy fields using two treatment methods: before transplanting (BT) and at sowing (AS). Uncertainty and sensitivity analyses were used to evaluate the robustness of the concentrations predicted by the model. RESULTS: The hourly predicted concentrations of imidacloprid and fipronil were accurate in both paddy water and 1 cm deep paddy soil. The coefficient of determination and Nash–Sutcliffe model efficiency were greater than 0.87 and 0.60 respectively. The 95th percentiles of the predicted concentrations of fipronil and imidacloprid indicated that the influence of input uncertainty was minor in paddy water but important in paddy soil. The pesticide deposition rate and the desorption rate from the root zone were identified to be the major contributors to the variation in the predicted concentrations in paddy water and soil. CONCLUSION: The PCPF‐NB model was validated for predicting the fate and transport of NB‐applied fipronil and imidacloprid using the BT and AS treatment methods. © 2015 Society of Chemical Industry